Comparison of control strategies for a solar heating system with underground pit seasonal storage in the non-heating season. (December 2019) - Li, Xiaoxia; Wang, Zhifeng; Li, Jinping; Yang, Ming; Yuan, Guofeng; Bai, Yakai; Chen, Longfei; Xu, Tao; Gilmanova, Alina
Highlights: A novel heating system with seasonal thermal energy storage was proposed. The system model was validated by experimental data. The impacts of three control strategies on system performance were analysed. Collection efficiency and storage performance were significantly improved. Abstract: The solar heating system coupled with seasonal thermal storage (SHSSTS) is a promising solution to solve the seasonal mismatch between the solar energy supply and heating demand. The performance of SHSSTS in the non-heating season has a vital impact on the discharging process during the heating season, not only the quantity of energy, but also the level of energy. The aim of this work is to analyze the impact of different control strategies on the performance of the system during the non-heating season by means of both experiments and simulation methods. A pilot solar heating system integrating with a 3000 m 3 underground water pit seasonal storage (UWPS) was built in Hebei, China. A calibrated system model was established in TRNSYS. Good agreement between measurement and simulation was obtained. The solar collection efficiency, stratification of the UWPS, energy storage efficiency and exergy storage efficiency were demonstrated for evaluating the system performance. Results showed that the control strategies were significant for improving the heat collection performance of solar receiver and the exergy efficiency of the UWPS. The stratification of the seasonal storage has an impact on the collection efficiency of the receiver, especially at the end of the non-heating season. In addition, at the end of the non-heating season in typical year, the solar collection efficiency could be increased by 10% in variable flow control compared to the temperature difference control.